2009
DOI: 10.1053/j.ajkd.2009.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Serum Bicarbonate Levels and the Progression of Kidney Disease: A Cohort Study

Abstract: Background Animal models of kidney disease have linked metabolic acidosis with renal damage. The role of low serum bicarbonate levels in kidney disease progression in humans has not been studied. Study Design Retrospective cohort study. Setting & Participants: Adults visiting a medical clinic in the Bronx, NY from 01/01/01 to 12/31/03 were included in the study (n=5,422) and followed until 6/30/07 Predictor Serum bicarbonate levels Outcomes Kidney disease progression was defined as either a decline in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
205
1
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 251 publications
(221 citation statements)
references
References 32 publications
5
205
1
10
Order By: Relevance
“…They reinforce the findings of earlier studies that have shown beneficial effects of alkali supplementation in slowing the progression of kidney disease 7,8 and studies documenting the association of metabolic acidosis with CKD progression. 15,16 We noted an association of DAL and progression to ESRD for participants with albuminuria. Our findings are in accordance with previous studies that have shown high consumption of meat food groups (i.e., each serving per day greater intake of the sum of red meat, processed meat, poultry, and fish) to be positively associated with albuminuria.…”
Section: Discussionmentioning
confidence: 87%
“…They reinforce the findings of earlier studies that have shown beneficial effects of alkali supplementation in slowing the progression of kidney disease 7,8 and studies documenting the association of metabolic acidosis with CKD progression. 15,16 We noted an association of DAL and progression to ESRD for participants with albuminuria. Our findings are in accordance with previous studies that have shown high consumption of meat food groups (i.e., each serving per day greater intake of the sum of red meat, processed meat, poultry, and fish) to be positively associated with albuminuria.…”
Section: Discussionmentioning
confidence: 87%
“…Low serum bicarbonate concentrations have been identified as a marker of CKD progression independent of eGFR. 20 Similarly, neutrophil gelatinaseassociated lipocalin, a marker of kidney tubule cell damage originally identified in AKI studies, 21 has been associated with interstitial fibrosis and tubular atrophy in renal biopsies in community-living patients with CKD. 22 Moreover, higher urine neutrophil gelatinase-associated lipocalin concentrations were recently associated with incident development of CKD in community-living individuals without AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Even among individuals without kidney disease, a lowgrade acidosis contributes to bone breakdown and possibly loss of muscle mass (9,10), and low-normal serum bicarbonate levels have been associated with lesser muscle strength and cardiovascular fitness, greater insulin resistance, and faster progression of kidney disease (6,7,13,26). Interventions to treat acidosis, including dietary modifications (27,28), may be most efficacious among older persons, in whom the capacity to excrete the daily acid load from modern Western diets is diminished.…”
Section: Discussionmentioning
confidence: 99%